Loss of Orai2-Mediated Capacitative Ca2+ Entry Is Neuroprotective in Acute Ischemic Stroke. Issue 11 (November 2019) - Stegner, David; Hofmann, Sebastian; Schuhmann, Michael K.; Kraft, Peter; Herrmann, Alexander M.; Popp, Sandy; Höhn, Marlen; Popp, Michael; Klaus, Vanessa; Post, Antonia; Kleinschnitz, Christoph; Braun, Attila; et al.
Abstract : Background and Purpose—: Ischemic stroke is one of the leading causes of disability and death. The principal goal of acute stroke treatment is the recanalization of the occluded cerebral arteries, which is, however, only effective in a very narrow time window. Therefore, neuroprotective treatments that can be combined with recanalization strategies are needed. Calcium overload is one of the major triggers of neuronal cell death. We have previously shown that capacitative Ca 2+ entry, which is triggered by the depletion of intracellular calcium stores, contributes to ischemia-induced calcium influx in neurons, but the responsible Ca 2+ channel is not known. Methods—: Here, we have generated mice lacking the calcium channel subunit Orai2 and analyzed them in experimental stroke. Results—: Orai2-deficient mice were protected from ischemic neuronal death both during acute ischemia under vessel occlusion and during ischemia/reperfusion upon successful recanalization. Calcium signals induced by calcium store depletion or oxygen/glucose deprivation were significantly diminished in Orai2-deficient neurons demonstrating that Orai2 is a central mediator of neuronal capacitative Ca 2+ entry and is involved in calcium overload during ischemia. Conclusions—: Our experimental data identify Orai2 as an attractive target for pharmaceutical intervention in acute stroke. Abstract : Supplemental Digital Content is available in the text.